PENGARUH REPUTASI BRAND DAN PENGALAMAN PENGGUNA TERHADAP KEPUTUSAN PEMBELIAN ONLINE DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING PADA WEBSITE PT XYZ - Edgar Maulana; Dwi Sunu Kanto (Jurnal Riset Multidisiplin Edukasi, 2025)
The rapid development of e-commerce in the fashion sector has intensified competition, making brand reputation, user experience (UX), and consumer trust strategic factors influencing online purchasing decisions. This study aims to analyze the impact of brand reputation and user experience on online purchasing decisions, with trust as a mediating variable for consumers of PT XYZ. The research adopts a quantitative design with a survey approach, involving 82 respondents who have made purchases at PT XYZ. Data was collected using a Likert scale questionnaire and analyzed with PLS-SEM. The results indicate that brand reputation significantly influences trust, but not directly the purchasing decision, while user experience significantly affects both trust and purchasing decisions. Trust was found to be an important mediating variable, with full mediation in the relationship between brand reputation and purchasing decisions and partial mediation in the relationship between user experience and purchasing decisions. This research provides implications for e-commerce management to focus on brand reputation and UX in building consumer trust.